Homozygous TAF1C variants are associated with a novel childhood‐onset neurological phenotype. Issue 5 (25th August 2020) - Knuutinen, Oula; Pyle, Angela; Suo‐Palosaari, Maria; Duff, Jennifer; Froukh, Tawfiq; Lehesjoki, Anna‐Elina; Kangas, Salla M.; Cassidy, James; Maraqa, Latifa; Keski‐Filppula, Riikka; Kokkonen, Hannaleena; Uusimaa, Johanna; et al.
Abstract: TATA‐box binding protein associated factor, RNA polymerase I subunit C ( TAF1C ) is a component of selectivity factor 1 belonging to RNA polymerase I (Pol I) transcription machinery. We report two unrelated patients with homozygous TAF1C missense variants and an early onset neurological phenotype with severe global developmental delay. Clinical features included lack of speech and ambulation and epilepsy. MRI of the brain demonstrated widespread cerebral atrophy and frontal periventricular white matter hyperintensity. The phenotype resembled that of a previously described variant of UBTF, which encodes another transcription factor of Pol I. TAF1C variants were located in two conserved amino acid positions and were predicted to be deleterious. In patient‐derived fibroblasts, TAF1C mRNA and protein expression levels were substantially reduced compared with healthy controls. We propose that the variants impairing TAF1C expression are likely pathogenic and relate to a novel neurological disease. This study expands the disease spectrum related to Pol I transcription machinery, associating the TAF1C missense variants with a severe neurological phenotype for the first time. Abstract :